Modified immersion suits for helicopter aircrew: evidence for improved conspicuity from sea trials - Nixon, Jim; Hodgkinson, Jane; Bennett, Christopher (Elsevier, 2020)
In this article we evaluate a modified immersion suit for use by helicopter aircrew. Helicopter aircrew operating over water are subject to international regulations which govern the personal protective equipment and clothing worn. Our modification increases the area of retroreflective material in a unique configuration. Highly reflective materials can cause unwanted reflections in the cockpit and data as to their efficacy in improving conspicuity in rescue at sea has not previously been captured. In this study we address this problem. Two methods were developed to test the acceptability and efficacy of a modified immersion suit to improve conspicuity in rescue operations at sea. Firstly, land-based trials employing subject matter experts were conducted to assess the tolerability of reflections in the cockpit from the modifications made to the immersion suit. Secondly, trials at sea using UK search and rescue teams captured data to assess the efficacy of the modification. Our results provide preliminary evidence for the acceptability of the modified immersion suit design and that the modification improves conspicuity in night time conditions, measured using the distance at which a target is detected. Our results support re-examination of the standard associated with passive lifesaving systems in helicopter aircrew immersion suit design to include an increase in the area of retroreflective material in the proposed novel configuration. Finally, our results support the use of coloured retroreflective tape to provide increased visual contrast, especially where this colour is coordinated with the main suit fabric.
Keywords: Conspicuous; Search and rescue; Helicopter; Immersion suit; Retroreflection; Lifesaving